Необходимые условия оптимальности в одной дискретной задаче управления с нелокальными краевыми условиями - Мансимов, К.Б. (Проблемы управления и информатики, 2012)
Розглянуто задачу оптимального керування, описану системою нелінійних різницевих рівнянь із нелокальними крайовими умовами. Застосовано модифіковану процедуру методу приросту, доведено необхідну умову оптимальності типу дискретного принципу максимуму Понтрягіна. An optimal control problem described by a system of nonlinear difference equations with nonlocal boundary conditions is considered. Applying the modified procedures of the increment method, the necessary optimality condition of type of Pontryagin’s discrete maximum principle is proved. The case of degeneration of the discrete maximum principle is studied separately.